2021
DOI: 10.1098/rsos.201822
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of cyclotetrapeptide analogues of c-PLAI and evaluation of their antimicrobial properties

Abstract: Antimicrobial peptides (AMPs) are interesting compounds owing to their ability to kill several pathogens. In order to identify new AMPs, c-PLAI analogues were synthesized and evaluated together with their linear precursors for their antimicrobial properties against two Gram-positive bacteria ( Staphylococcus aureus and Bacillus cereus ), two Gram-negative bacteria ( Escherichia coli and Klebsiella pneumoniae ), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…SPPS was used to synthesize the linear precursor of cyclopurpuracin, which was then cyclized in solution phase. The combination of these methods has been shown to provide cyclopeptides with high purity and yield, as reported by Muhajir et [15], dianthin I synthesis reported by Zhang et al [16] and total synthesis of exumolide A and B reported by Rahmadani et al [17] To obtain a protected-linear precursor, the Fmoc/t-Bu strategy of the orthogonal protecting group was applied in the SPPS. The Fmoc is the protecting group of the α amino group, while t-Bu is the protecting group of the side chain for the serine residue.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…SPPS was used to synthesize the linear precursor of cyclopurpuracin, which was then cyclized in solution phase. The combination of these methods has been shown to provide cyclopeptides with high purity and yield, as reported by Muhajir et [15], dianthin I synthesis reported by Zhang et al [16] and total synthesis of exumolide A and B reported by Rahmadani et al [17] To obtain a protected-linear precursor, the Fmoc/t-Bu strategy of the orthogonal protecting group was applied in the SPPS. The Fmoc is the protecting group of the α amino group, while t-Bu is the protecting group of the side chain for the serine residue.…”
Section: Introductionmentioning
confidence: 96%
“…SPPS was used to synthesize the linear precursor of cyclopurpuracin, which was then cyclized in solution phase. The combination of these methods has been shown to provide cyclopeptides with high purity and yield, as reported by Muhajir et al in 2021 in synthesizing Nocardiotide A [13], Kurnia et al in 2022 in synthesizing Xylapeptide B [14], Maharani et al in 2021 in synthesizing c‐PLAI [15], dianthin I synthesis reported by Zhang et al [16] and total synthesis of exumolide A and B reported by Rahmadani et al [17]…”
Section: Introductionmentioning
confidence: 99%
“…The different experimental conditions (different assay systems, different strains, and different growth conditions) could affect the results of the biological activity test [20]. Furthermore, the discrepancy in the activities of the natural versus synthetic peptides may be because synthetic proline-containing cyclopeptides could possess different biological properties despite being chemically similar due to the conformational change in the proline unit [17,[21][22][23]. In addition, there may be differences in the purity between synthetic and natural products.…”
Section: Resultsmentioning
confidence: 99%
“…Herein, we report the first total synthesis of xylapeptide A by a combination of solid‐ and solution‐phase methods, which have been employed to synthesize several cyclopeptides such as analogues of C‐PLAI [17], nocardiotide A [18], and xylapeptide B [4]. A Fmoc strategy with 2‐chlorotrityl chloride resin as a solid support was used to synthesize the linear precursor of xylapeptide A and a head‐to‐tail cyclization to obtain xylapeptide A in the solution‐phase.…”
Section: Introductionmentioning
confidence: 99%
“…In this strategy, a linear precursor is prepared through solid-phase synthesis, while cyclisation is performed in a solution. This method was applied by Muhajir et al in 2021 for the synthesis of nocardiotide A [ 12 ], Kurnia et al in 2022 for the synthesis of xylapeptide B [ 13 ], Maharani et al in 2021 for the synthesis of c-PLAI analogues [ 14 ], Zhang et al in 2016 for the synthesis of dianthin I [ 15 ], and Rahmadani et al in 2021 for the synthesis of exumolide A and B [ 16 ], as well as Yayat et al in 2022 for the synthesis of reversed cyclopurpuracin, as mentioned earlier [ 11 ]. The latter strategy was applied in current studies.…”
Section: Introductionmentioning
confidence: 99%